2015
DOI: 10.1039/c5ra05107j
|View full text |Cite
|
Sign up to set email alerts
|

Natural-gel derived, N-doped, ordered and interconnected 1D nanocarbon threads as efficient supercapacitor electrode materials

Abstract: Natural gel pectin is transformen into interconnected, N-doped, ordered and Interconnected 1D nano-carbon threads upon high temperature pyrolysis inside SBA-15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…[115,116,120] The high surface areas achievable from these carbon typeso ffer ah igh apparent electrochemical area for potential-dependents urface ad-sorption, and hence,h igh capacitance. [127,139,140] In this regard, some silica-basedt emplates with suitable porosity have become importanto ver the years. [115,137] Provision for the inclusion of heteroatom doping in the carbon matrix, throught he use of as uitable pyrolysis strategy,h as been further beneficial for improvingt he capacitance values through pseudocapacitance contributions.…”
Section: Other Applications Of Hard Carbonsmentioning
confidence: 99%
See 2 more Smart Citations
“…[115,116,120] The high surface areas achievable from these carbon typeso ffer ah igh apparent electrochemical area for potential-dependents urface ad-sorption, and hence,h igh capacitance. [127,139,140] In this regard, some silica-basedt emplates with suitable porosity have become importanto ver the years. [115,137] Provision for the inclusion of heteroatom doping in the carbon matrix, throught he use of as uitable pyrolysis strategy,h as been further beneficial for improvingt he capacitance values through pseudocapacitance contributions.…”
Section: Other Applications Of Hard Carbonsmentioning
confidence: 99%
“…[116] For these applications, high-surface-area alternatives have attracted particulara ttention, owing to the availability of maximum exposed surface for catalysis and surface adsorption. [117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] Heteroatom-doped carbon systems have shown promising activity as ORR catalysts for applicationsi nf uel cells, and a number of modified hard carbons have been reported with commendable performances as electrocatalysts for the ORR. [133] Doping of various heteroatoms and their codoping have been shown to enhance the activity,r elative to undoped systems.…”
Section: Other Applications Of Hard Carbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has promoted the exploration of sophisticated materials, especially hybrid organic-inorganic compounds. Wahid et al 48 reported the template based synthesis of supercapacitive carbon by inltrating a natural hydrogel, pectin, into a mesoporous silica template and, subsequently, applying pyrolysis in an inert atmosphere (SBA-15). Pectin is an indigestible soluble ber that, combined with water, forms colloidal systems and gels and are frequently used as ingredients in food technology (e.g.…”
Section: Other Polysaccharidesmentioning
confidence: 99%
“…Indeed, pectin hydrogel gives place to unbreakable columns inside silica channels with less sideways diffusion, fullling all the necessary requirements for the transformation into one dimensional carbon threads. Wahid et al 48 doped the carbonpectin activated electrodes with urea molecules, which also increased the viscosity due to the formation of urea-pectin chain interactions. Indeed, the compactness of the electrode increased with the viscosity since the sideways ow decreased, even at higher temperatures.…”
Section: Other Polysaccharidesmentioning
confidence: 99%